Early Treatment Response Monitoring Using 2-Deoxy-2-[18F]fluoro-D-glucose Positron Emission Tomography Imaging during Fractionated Radiotherapy of Head Neck Cancer Xenografts. (28th April 2014) - Huang, Jiayi; Chunta, John L.; Amin, Mitual; Lee, David Y.; Grills, Inga S.; Oliver Wong, Ching-Yee; Marples, Brian; Yan, Di; Wilson, George D.
Abstract : Background. To determine the optimal timing and analytic method of 2-deoxy-2-[ 18 F]fluoro-D-glucose positron emission tomography (PET) imaging during fractionated radiotherapy (RT) to predict tumor control. Methods. Ten head neck squamous cell carcinoma xenografts derived from the UT-14-SCC cell line were irradiated with 50 Gy at 2 Gy per day over 5 weeks. Dynamic PET scans were acquired over 70 minutes at baseline (week 0) and weekly for seven weeks. PET data were analyzed using standard uptake value (SUV), retention index (RI), sensitivity factor (SF), and kinetic index (Ki). Results. Four xenografts had local failure (LF) and 6 had local control. Eighty scans from week 0 to week 7 were analyzed. RI and SF after 10 Gy appeared to be the optimal predictors for LF. In contrast, SUV and Ki during RT were not significant predictors for LF. Conclusion. RI and SF of PET obtained after the first week of fractionated RT were the optimal methods and timing to predict tumor control.